Interventions to reduce the stunting prevalence in children under five through nutrition education: A systematic review - Amanto, Adibah Rasikhah (BKM Public Health and Community Medicine, 2021)
Objective: To determine the effectiveness of nutrition education in increasing child growth and development and reducing the stunting prevalence in children under five years old. Method: The study used Cochrane Collaboration Methodology and Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). The literature search used three electronic bibliographic databases, the Wiley Online Library, Public Health, or gray literature Electronic Thesis/Dissertation Universitas Gadjah Mada. Researchers independently did the abstract screening process, data extraction, and bias assessment. Some of the keywords used in the literature search were nutrition training/education, Infant and Child Feeding (PMBA), cadres, and growth. Results: We analyzed the effectiveness of nutrition education in three studies that met the inclusion criteria from 39 collected papers using external factors, such as changes in children's intake and growth and development. We found several strategy methods in nutrition education that could improve the implementation of stunting prevention programs, such as routine home visits by cadres, regular monitoring and evaluation, and PMBA practices. In several studies, nutrition education classes can increase the intake of children under five and reduce the prevalence of stunting. Several studies still need to be added to see the effectiveness of nutrition education in areas with different population characteristics. Conclusion: Interventions in the form of nutrition education, either in lecture, practice, or discussion, can increase the nutritional intake of children under five, as seen in the improvement in nutritional status, behavioral development, or reduced number of malnutrition and stunting prevalence. However, it is still necessary to use targeted methods and materials according to the needs of educational targets to achieve maximum results.